Long non-coding RNA LncMPEG1 responds to multiple environmental stressors by affecting biomineralization in pearl oyster Pinctada fucata martensii - Cai, Caixia; He, Qi; Xie, Bingyi; Xu, Zhijie; Wang, Cheng; Yang, Chuangye; Liao, Yongshan; Zheng, Zhe (Frontiers in Marine Science, 2022)
Marine environmental change directly affects bivalve growth and survival. Exoskeleton formation, the main energy dissipation in the physiological metabolism, typically reflects the body growth of the bivalve. However, how bivalves regulate the biomineralization of the exoskeleton under environmental stressors is not yet clear. Long non-coding RNA regulates various life processes through complex mechanisms in vertebrates and invertebrates. In this research, we cloned the complete sequence of a mantle-specific expressed long non-coding RNA (designated as LncMPEG1) from a pearl oyster, Pinctada fucata martensii. A quantitative real-time PCR analysis showed that LncMPEG1 expression was significantly high in early umbo larvae and juveniles, which would be the critical periods of shell development. LncMPEG1 was identified in the outer epithelium of the middle fold from the mantle edge, mantle pallial, and mantle center by using in situ hybridization. Additionally, the expression of LncMPEG1 was stimulated by shell damage, alien invasion, heat and cold temperature stress, and hypoxia stress. In the mantle, a decreased in LncMPEG1 expression was detected by RNA interference, which can cause the irregular growth of crystals on the inner surface of the prismatic layer and nacre in the shells. Therefore, we propose that LncMPEG1 could be a key regulator in biomineralization and responds to environmental stress in the mantle .